Técnicas de rehabilitación pulmonar y su influencia en el tratamiento de las neumonías en adultos mayores ingresados en la unidad de cuidados intensivos. Hospital Iess. Babahoyo. Los Ríos. primer semestre 2018. - De Mora García, Stephany Gabriela (2018)
The research project deepens in a frequent low respiratory pathology, pneumonia, which can be of infectious or non-infectious cause which mainly affects adults older than 65 years. To establish the influence of pulmonary rehabilitation techniques in the treatment and prevention of complications derived from pneumonias in older adults admitted to the Intensive Care Unit of IESS Babahoyo Hospital of Los Ríos Province. First semester 2018. An exploratory and descriptive field study was carried out using the non-experimental method, with a qualitative-quantitative approach. The universe of study was 135 elderly people who entered the IESS Hospital of the Babahoyo Canton of Los Ríos Province during the first semester of 2018 and the study sample was 33 people. Intentional non-probabilistic sampling was used. The technique of unstructured and direct scientific observation, the unstructured interview and the survey to gather information were applied. 80% of the sample admitted with acute respiratory infections and 20% presented a diagnosis of pneumonia. The respiratory therapists manifested in a 100% that, if they know about the importance of the application of pulmonary rehabilitation techniques and if they apply them to patients with pneumonia, but in the direct observation made it was possible to identify that it is not done with the necessary frequency. The application of pulmonary rehabilitation techniques is considered of great importance for the prompt improvement of the patient, although they are not applied with the necessary frequency, since there is no adequate follow-up and evaluation of their results.